Effects of focal vibration on power and work in multiple wingate tests - Guido Filippi; Luigi Fattorini; Aurora Summa; Alessandro Zagaglia; Angelo Rodio (Termedia Publishing House, 2019)
The aim of the study was to assess the effects of a specific protocol, based on a focal muscle vibration, on mechanical parameters in an exercise composed of five repeated bouts of sprint interval tests (Wingate Anaerobic Tests, 10 seconds duration). Twenty-eight young male healthy subjects were randomized to two groups (VIB and CTRL). Peak power (PP), average peak between bouts (aP) and total exercise work (TW) were measured. In both groups, three different exercise sessions were carried out, interspersed by seven days: T0, T1 and T2. Between the baseline (T0) and T1, in the VIB group the intervention was administered on three successive days on quadriceps muscles, whereas a placebo administration was carried out in the CTRL group at the same time. At T1 (30 minutes after intervention) and T2 (7 days after) CTRL did not show any significant change, whereas VIB showed significant increases in PP (11.4%-9.3%), aP (6.6%-6.9%) and TW (5.7%-7.9%) with respect to T0. The results could be explained by an ameliorative agonist-antagonist balance, and this hypothesis is coherent with the literature. On the basis of the present findings, the investigated intervention might be usefully adopted to increase muscular power and endurance.